Egocentrismo y altruismo en la comunicación humana: algunas consideraciones psicodinámicas - Ramírez, Luis (1998)
This paper is an analysis of human communication from the concepts of "egocentrism" and altruism", concepts derived from the basic dynamism inherent to behavior functioning. A person, from its own ontologica structure is necessarily and existentially induced to gradually contemplate, understand and internalize its own the reality and reality of others. Thus the constant, intense and simultaneo us presence of two tendencies: "self-retreat" and self-transcendence". The elaboration of those lines of dynamic orientacion are approached in their defensive cannotations. Finally, the autor discusses the essential implications of a genuine altruistic attitude of the subject in relation to others.